Psychological Effects of Game Activities in Developing the Attention of Preschool Children - Hamroeva Lobar Olimjonovna (Zien Journals, 2021)
The article discusses the process of attention in preschool children and its psychological impact on the individual in relation to play activities
Keywords: Person; crisis; game activity; program; neglect; games